Determinants of donor generosity: A survey of the aid budget literature - Andreas Fuchs; Axel Dreher; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2012)
What determines the foreign aid effort of donor countries? We review the existing literature on donors' aid budgets and examine which of the suggested variables robustly determine aid effort, measured as Official Development Assistance (ODA) as a share of gross national income. More specifically, we empirically test 16 hypotheses using panel econometric methods for member countries of the Development Assistance Committee (DAC) in the 1976-2008 period. To test for the robustness of our results, we extend our dataset to 48 possible determinants of aid budgets and apply an Extreme Bounds Analysis (EBA). In our fixed effects regressions, we find that aid inertia, the donor country's GDP per capita, the existence of an independent aid agency, and colonial history have a robust and quantitatively relevant impact on countries' aid efforts. Among the potential substitutes for aid, remittances exert a robust effect. Excluding year fixed effects, political globalization, Russian military capacity, peer effects, aid effectiveness, and government debt also play a significant role.
Keywords: F35; H81; H87; 330; Foreign aid; Official Development Assistance; Aid budget; Extreme Bounds Analysis; Entwicklungshilfe; Öffentliche Ausgaben; Schätzung; Industriestaaten